An International Observational Prospective Survey Assessing the Control of Atrial Fibrillation in Asia-Pacific: Results of the Record-AFAP Registry - Amerena, John; Chen, Shih-Ann; Sriratanasathavorn, Charn; Cho, Jeong-Gwan; Dejia, Huang; Omar, Razali; Fat, Tse Hung; King, Anthony (Clinical Medicine Insights. Cardiology, 2015)
A prospective 1-year observational survey was designed to assess the management and control of atrial fibrillation (AF) in eight countries within the Asia-Pacific region. Patients (N = 2,604) with recently diagnosed AF or a history of AF ≤1 year were included. Clinicians chose the treatment strategy (rhythm or rate control) according to their standard practice and medical discretion. The primary endpoint was therapeutic success. At baseline, rhythm- and rate-control strategies were applied to 35.7% and 64.3% of patients, respectively. At 12 months, therapeutic success was 43.2% overall. Being assigned to rhythm-control strategy at baseline was associated with a higher therapeutic success (46.5% vs 41.4%; P = 0.0214) and a lower incidence of clinical outcomes (10.4% vs 17.1% P < 0.0001). Patients assigned to rate-control strategies at baseline had higher cardiovascular morbidities (history of heart failure or valvular heart disease). Cardiovascular outcomes may be less dependent on the choice of treatment strategy than cardiovascular comorbidities.